Performance Analysis of a Cellular-Based Non-Terrestrial Network Mobility Management Method to Support Continuous Service - Yu, Jina; Baik, Jong Soo; Kim, Jae Hyun (Journal of Korean Institute of Communications and Information Sciences, 2022)
In this paper, we implement a cellular-based non-terrestrial network (NTN) to support continuous service and to analyze the performance of the service connection method using user equipment (UE) location information. The location-based mobility management method uses the distance from the cell center point to the cell edge as an index, and the intersection point of the serving cell and the neighboring cell is used as a criterion for handover measurement report triggering. In addition, mobility management method process is divided into 3 states in order to analyze the performance of the event of reference signal received power (RSRP)-based mobility management method and the event of location-based mobility management method in detail. According to simulation results, compared to the terrestrial network (TN), the mobility management method in the NTN has a low ping-pong rate due to its fast mobility.
Keywords: Cellular; Handover; LEO satellite; NTN; Satellite communication